Pemberdayaan Bank Sampah Dayung Habibah melalui Edukasi dan Pembuatan Eco Enzyme serta Diversifikasi Produknya - Yuliawati, Yuliawati; Kasmadi, Fathnur Sani; Maritsa, Hasnaul (Jurnal Abdimas Kesehatan (JAK), 2025)
The increasing volume of household organic waste remains a challenge in many communities, including Legok Village, Jambi. This community engagement program aimed to enhance local residents’ knowledge and skills in organic waste management through the production of eco-enzyme and its derivative products. The methods applied included education, interactive discussions, and hands-on training in producing eco-enzyme, dishwashing soap, floor cleaner, liquid organic fertilizer, compost, and compress pads. Evaluation was conducted using pre- and post-tests to measure knowledge improvement, as well as a satisfaction survey to assess participants’ acceptance. Results showed a significant increase in knowledge, with average scores rising from 54 (pre-test) to 84 (post-test), representing a 55.5% improvement. Participants successfully followed all stages of eco-enzyme preparation, from material selection and mixing to the initial fermentation process, and demonstrated the ability to independently produce eco-enzyme and its derivatives at home. This program effectively improved environmental literacy, awareness, and motivation among the community in managing household waste. Furthermore, it created opportunities for eco-friendly entrepreneurship based on a circular economy, supporting sustainable development goals (SDGs).